Welcome to management how to grow from top performer to excellent leade - Ryan Hawk (New York New McGraw-Hill, 2020)
"From the creator and host of The Learning Leader Show, 'the most dynamic leadership podcast out there' (Forbes) that will 'help you lead smarter'(Inc.), comes an essential tactical guide for newly promoted managers. Every year, millions of top performers are promoted to management-level jobs-only to discover that the tactics that got them promoted are not the tactics that will make them effective in their new role. In Welcome to Management, Ryan Hawk provides practical, actionable advice and tools designed to ensure that transition is a successful one"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Management